Ban Treaty: will it abolish nuclear weapons? A Japanese perspective. Issue 2 (4th May 2018) - Abe, Nobuyasu
ABSTRACT: In so far as the nuclear-weapons possessors do not accept the Ban Treaty, practically it will not reduce nuclear weapons nor abolish them as a matter of law. However, if the treaty is accepted by an overwhelming majority of states, it will significantly strengthen the norm against the nuclear weapons. A norm binds everybody irrespective of legal acceptance of a treaty. Thus, it exposes any violator to the risk of international punishment. The Ban Treaty will help bring the movement towards nuclear abolition forward and reduce incentives to own nuclear weapons. The international humanitarian law that was the main basis for the Ban Treaty needs to be upheld firmly. The set of norms under international humanitarian law will serve to limit the justifiable cases where nuclear weapons can ever be used. The Non-Proliferation Treaty and the efforts to prevent nuclear proliferation must be sustained even after the Ban Treaty comes into force.